2023
DOI: 10.3389/fnbeh.2023.1085404
|View full text |Cite
|
Sign up to set email alerts
|

Restricted and repetitive behaviors and their developmental and demographic correlates in 4–8-year-old children: A transdiagnostic approach

Abstract: Background: Restricted and repetitive behaviors (RRBs) are a broad class of behaviors characterized by frequent action repetition and intense preference for sameness. Research has predominantly focused on RRBs in diagnosed clinical groups, particularly in autism spectrum disorder and genetic disorders. Using a transdiagnostic approach, the current study examined RRBs in a diverse sample of children in relation to developmental and demographic correlates (age, language, non-verbal ability, child anxiety, sex, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 61 publications
2
6
1
Order By: Relevance
“…No data are collected on whether children eventually receive a clinical diagnosis because the NDAU is concerned with identifying patterns of psychological functioning and behavior to help schools understand each child's profile. Language data for these children have previously been reported (Keating et al, 2023;Paine et al, 2021) showing that most children have verbal and non-verbal ability in the average range within 1 SD from the mean (see Keating et al, 2023, Table 1 and Figure S1). Among 4-to 7 year-olds olds, 20.9% had below average BPVS scores (1 SD below mean), 6.4% had below average Lucid Verbal Reasoning scores (Singleton, 2001) Data for children aged 6 and 7 years were selected for this study, to facilitate the same age range across the two samples.…”
Section: Community Sampled Groupmentioning
confidence: 81%
See 2 more Smart Citations
“…No data are collected on whether children eventually receive a clinical diagnosis because the NDAU is concerned with identifying patterns of psychological functioning and behavior to help schools understand each child's profile. Language data for these children have previously been reported (Keating et al, 2023;Paine et al, 2021) showing that most children have verbal and non-verbal ability in the average range within 1 SD from the mean (see Keating et al, 2023, Table 1 and Figure S1). Among 4-to 7 year-olds olds, 20.9% had below average BPVS scores (1 SD below mean), 6.4% had below average Lucid Verbal Reasoning scores (Singleton, 2001) Data for children aged 6 and 7 years were selected for this study, to facilitate the same age range across the two samples.…”
Section: Community Sampled Groupmentioning
confidence: 81%
“…Evidence on the association between language and RRBs in non-autistic children is sparse. While one study with two-year-olds found that semantic language (vocabulary comprehension) was associated with one subtype of RRB (RSMB) (Larkin et al, 2017), another study with older children found no association (Keating et al, 2023). Pragmatic language was not tested in either of these studies.…”
Section: The Relationship Between Pragmatic Difficulties and Rrbsmentioning
confidence: 94%
See 1 more Smart Citation
“…The study did not, however, directly compare the broad constructs of IS and RSM RRBs, nor did it examine internalising behaviours more generally, or include any measure of externalising behaviours. More recently, Keating, Van Goozen, Uljarević, Hay, & Leekam et al (2023) recruited 4-to 8-year-old children with non-specific behavioural and emotional difficulties manifested in school. In this cross-sectional study, they found that both RSM and IS (measured by the RBQ-2) were significantly associated with both broad internalising and externalising scores on the Strengths and Difficulties Questionnaire (SDQ; Goodman, 1997), as well as with the specific emotion, conduct, hyperactivity, and peer-relations subscales.…”
Section: Of 10mentioning
confidence: 99%
“…Previous research indicates that RRBs are associated with socio-economic status (SES) in community samples (Larkin et al, 2017;Leekam et al, 2007); SES was therefore measured and controlled for in all analyses. Moreover, although evidence of sex differences in RRBs is somewhat limited (for review, see Uljarević et al, 2023), a recent study with 4-to 8-year-old children referred for assessment of emotional or behavioural difficulties reported that boys had significantly higher rates of both IS and RSM RRBs than girls (Keating et al, 2023).…”
Section: Of 10mentioning
confidence: 99%